Evaluation of physicochemical and antioxidant properties of two stingless bee honeys: a comparison with Apis mellifera honey from Nsukka, Nigeria - Justus Amuche Nweze; J. I. Okafor; Emeka I. Nweze; Julius Eyiuche Nweze (BMC Research Notes, 2017)
Abstract Objective Several physical, biochemical and antioxidant properties of two Nigerian stingless bee honey varieties (Melipona sp. and Hypotrigona sp.) were compared with Apis mellifera honey using standard analytical procedures. Results The mean pH of Apis mellifera, Hypotrigona sp. and Melipona sp. honeys were 4.24 ± 0.28, 3.75 ± 0.11 and 4.21 ± 0.37 respectively. The mean moisture contents of the honeys were 11.74 ± 0.47, 17.50 ± 0.80, and 13.86 ± 1.06%. Honey samples from Hypotrigona sp. when compared with other honey samples had the highest mean total dissolved solids (370.01 ± 22.51 ppm), hydroxymethylfurfural (16.58 ± 0.37 mg/kg), total acidity (35.57 ± 0.42 meq/kg), protein content (16.58 ± 0.37 g/kg), phenol content (527.41 ± 3.60 mg/kg), and ascorbic acid (161.69 ± 6.70 mg/kg), antioxidant equivalent—ascorbic acid assay value (342.33 ± 0.78 mg/kg) as well as ferric reducing power (666.88 ± 1.73 μM Fe(II)/100 g) (p < 0.05). Several strong correlations were observed among some of the parameters of the honeys. This is the first study to compare the properties of Nigerian honey bees. Our results suggested that these honeys (specifically Hypotrigona sp. honey) is a good source of antioxidants comparable to A. mellifera honey.